Americans [1940-2006] : The social landscape from 1940 until 2006. Masterpieces of American photography - Matt, Gerald; Weiermair, Peter (Wien : Kunsthalle Wien, 2006)
Arbus, Diane ; Avedon, Richard ; Clark, Larry ; Davidson, Bruce ; Frank, Robert ; Friedlander, Lee ; Hujar, Peter ; Levitt, Helen ; McGinley, Ryan ; Parks, Gordon ; Solomon, Rosalind ; Templeton, Ed ; Uzzle, Burk
Americans. Meisterwerke amerikanischer Fotografie 1940-2006, Kunsthalle Wien, 2006-11-03. 2007-02-04
boek
Keywords: U.S.A.